Peran Acara Pekan Kebudayaan Nasional terhadap Persepsi Mahasiswa tentang Kualitas Pendidikan Bahasa dan Sastra Indonesia - Melsa Nurpuzianah; Hindun Hindun (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
This research explores the role of the 2023 National Cultural Week (Pekan Kebudayaan Nasional - PKN) in shaping the perceptions of students majoring in Indonesian Language and Literature Education at UIN Syarif Hidayatullah Jakarta regarding the quality of literary education. Utilizing a qualitative approach, the study investigates student participation, highlighting a high interest in the "Tribute Jamal D. Rahman" and "Pojok Baca Danarto" events. Findings indicate that, although students initially rated the quality of literary education positively, participation in PKN enriched their understanding and appreciation of the diversity of Indonesian literature. The integration of cultural activities into the curriculum received strong support, while student suggestions emphasized the need for event development and broader community involvement. In conclusion, PKN successfully stimulated interest and provided an enriching experience that contributes to the enhancement of literary education. The implications suggest that future cultural events at universities should consider student feedback to ensure a more diverse and satisfying experience for participants.